Penyalahgunaan Akta Notaris dalam Skema Pailit Rekayasa - Rosiga, Fonnyta Laurenzia; Safirah, Asharin Sindy (WELFARE STATE Jurnal Hukum, 2025)
This study examines the engineered bankruptcy scheme carried out through the use of authentic deeds, thereby raising the need to review the role and responsibilities of notaries. A notarial deed has the nature of perfect evidentiary strength, yet in practice there is room for misuse, allowing such documents to facilitate bankruptcy petitions based on fictitious debts. The study highlights a case involving the use of a shell company to submit a debt suspension petition, illustrating the potential abuse within the legal system. By employing a normative approach and analyzing legal documents, the research underlines the urgency of stricter supervision over notarial practices and the necessity of stronger verification mechanisms in both company incorporation and the evidentiary process in bankruptcy proceedings. Furthermore, the study emphasizes the importance of notaries’ moral integrity in maintaining public trust in law. The findings recommend administrative reforms, enhanced professional standards, and reinforced oversight to prevent the misuse of formal legality for unlawful interests